2011
DOI: 10.1038/pj.2010.117
|View full text |Cite
|
Sign up to set email alerts
|

Complementary functionality of SiO2 and TiO2 in polyimide/silica–titania ternary hybrid nanocomposites

Abstract: A polyimide (PI) composite containing SiO 2 and TiO 2 hybridized nanoparticles was prepared by the sol-gel process. Polyamic acid (PAA) solution, the precursor of PI, was synthesized from 2,2¢-bis-(3,4-dicarboxyphenyl) hexofluoropropane dianhydride and bis [4-(3-aminophenoxy) phenyl sulfone in N-methyl-2-pyrrolidone. The SiO 2-TiO 2 hybrid nanoparticles were prepared by the sol-gel process in a PAA solution into which tetraethoxysilane, titanium (IV) tetrabutoxide and acetylacetone were mixed for subsequent hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…, the intensities of characteristic groups in the PAA spectra including N–H or O–H in the range 2500–3500 cm −1 and –NH 2 at 1650 cm −1 decrease with increasing temperature. Simultaneously, the growth of characteristic imide absorption bands at 725 cm −1 (cyclic CO bending), 1380 cm −1 (C–N stretching), 1720 and 1780 cm −1 (symmetric and asymmetric CO stretching) is observed. The characteristic imide absorption band at 725 cm −1 was chosen to estimate the degree of imidization of PAA at various temperatures because of less interference from the functional groups of anhydride, solvent and filler in this frequency range, based on a previous study.…”
Section: Resultsmentioning
confidence: 82%
“…, the intensities of characteristic groups in the PAA spectra including N–H or O–H in the range 2500–3500 cm −1 and –NH 2 at 1650 cm −1 decrease with increasing temperature. Simultaneously, the growth of characteristic imide absorption bands at 725 cm −1 (cyclic CO bending), 1380 cm −1 (C–N stretching), 1720 and 1780 cm −1 (symmetric and asymmetric CO stretching) is observed. The characteristic imide absorption band at 725 cm −1 was chosen to estimate the degree of imidization of PAA at various temperatures because of less interference from the functional groups of anhydride, solvent and filler in this frequency range, based on a previous study.…”
Section: Resultsmentioning
confidence: 82%
“…0.01 wt%, the transmittance at 550 nm was 91% for PI/GO-0.010 film, compared with 97% for pure PI. Liaw et al [10] also reported a fluorinated PI film with a thickness of 5 mm exhibited the transmittance at 500 nm of 97% and the transmittance decreased with the content of nanoparticles in PI matrix. Hence, in this study, the GO content was limited to only 0.01 wt% to remain sufficient optical transmittance of PI for practical applications.…”
Section: Optical Transparency Of Pure Pi and Pi/go Nanocompositesmentioning
confidence: 91%
“…As shown in Fig. 2, the characteristic imide absorption bands at 715 cm À1 (C]O bending), 1380 cm À1 (CeN stretching), 1716 and 1774 cm À1 (symmetrical and asymmetrical C]O stretching) [10,44] were presented on the IR spectrum of PI sample as the temperature reached 140 C. The characteristic imide absorption band at 715 cm À1 was chosen to estimate the imidization degree of PI precursors at different temperatures because there is less interference from the anhydride, catalyst and solvent functional groups in this frequency range. An internal standard at the frequency of 1500 cm À1 (C]C stretching in benzyl ring group) was selected to normalize the intensity of the above peak and hence to eliminate the effect of film thickness on the resultant intensity.…”
Section: Imidization Degree Of Pimentioning
confidence: 97%
“…These characteristic peaks are close to the data reported previously. [29][30][31][32] Comparing the two lines, there are no obviously different peaks. This finding suggests that a small amount of GO make no change to the chemical structure of GO/PI resin composite.…”
Section: Characterization and Morphology Of Go Neat Pi And Go/pi Resin Compositesmentioning
confidence: 97%